(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study is undertaken to find out the impact of digital story telling on the students’ engagement. It also attempts to find out the difference of perception between the teachers based on gender and locality. Normative survey method has been followed for the present study